The Higher Education Research - Introduction to IPPTN - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2003)
Institut Penyelidikan Pendidikan Tinggi Negara (National Higher Education Research Institute) was established by the National Council for Higher Education (MPTN) and was officially launched on the 21st August 1997.